Employee whistleblower protection: an analysis of Malaysian law - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig; Ahmed, Kyaw Hla Win @ Md Hassan (2015)
In Malaysia, the Whistleblower Protection Act 2010 (WPA) provides protection to a person in an organisation who exposes misconduct, alleged dishonest or illegal activity that violates the existing laws, among others. For example, alleged fraud, health and safety violations, and corruption, to name but a few. Undeniably, most whistleblowers are internal to an organisation who report misconduct of a fellow employee or superior within their company and they frequently face reprisal at the hands of the organisation which they have accused. In fact, many people do not consider blowing the whistle because of fear of retaliation and losing their relationships at workplace. Although whistleblowers are protected under law from employer retaliation, there have been many cases where punishment for whistle blowing has occurred, such as suspension, demotion, termination, or harsh mistreatment by other employees. Hence, this paper analyses the adequacy of the legal protection available to employees who whistle blow on their employers with reference to the WPA.